2024
DOI: 10.1002/hpja.858
|View full text |Cite
|
Sign up to set email alerts
|

Adapting and translating the ‘Hep B Story’ App the right way: A transferable toolkit to develop health resources with, and for, Aboriginal people

Paula Binks,
Cheryl Ross,
George Garambaka Gurruwiwi
et al.

Abstract: Issue AddressedIn 2014 the ‘Hep B Story App’, the first hepatitis B educational app in an Aboriginal language was released. Subsequently, in 2018, it was assessed and adapted before translation into an additional 10 Aboriginal languages. The translation process developed iteratively into a model that may be applied when creating any health resource in Aboriginal languages.MethodsThe adaptation and translation of the ‘Hep B Story’ followed a tailored participatory action research (PAR) process involving crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Success factors include: systematic data organisation, 17 regular CQI cycles, a hub and spoke model of care, a trained First Nations and PHC health workforce, 19 , 20 dedicated staffing, outreach access to diagnostic technology and in-language consumer health resources. 22 The Hep B PAST program consists of a diverse, multidisciplinary team that includes researchers, epidemiologists, public health experts, lab scientists, clinical doctors, nurses, Aboriginal health workers, and people living with CHB. This collaborative approach, coupled with a culture of true partnerships and flattened hierarchies, has been key to its success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success factors include: systematic data organisation, 17 regular CQI cycles, a hub and spoke model of care, a trained First Nations and PHC health workforce, 19 , 20 dedicated staffing, outreach access to diagnostic technology and in-language consumer health resources. 22 The Hep B PAST program consists of a diverse, multidisciplinary team that includes researchers, epidemiologists, public health experts, lab scientists, clinical doctors, nurses, Aboriginal health workers, and people living with CHB. This collaborative approach, coupled with a culture of true partnerships and flattened hierarchies, has been key to its success.…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of CHB care in PHC clinical care teams was implemented through systematic care planning, PHC workforce education, 19 , 20 CHB identified positions embedded in PHC, availability of ultrasound and FibroScan®, support by the specialist outreach teams 21 and culturally appropriate in-language consumer resources. 22 We have previously reported that having an educational tool in a person's first language is crucial to developing treatment partnerships for First Nations peoples living with CHB. 23 The “Hep B Story” app is available in nine Aboriginal languages, covering 70% of NT First Nations peoples in their first languages.…”
Section: Methodsmentioning
confidence: 99%
“…A straightforward word-for-word translation of a script risks misinformation and loss of context and meaning. Ensuring accurate conceptual transmission often entailed crafting and sharing stories to convey the message correctly [11].…”
Section: Concept Versus Languagementioning
confidence: 99%
“…It has a disproportionate impact on Aboriginal and Torres Strait Islander populations, with prevalence of 6% [4][5][6][7]. While socioeconomic factors, healthcare access, and language barriers can present challenges [8], recent research shows that communityled, systematic approaches to CHB management improve the cascade of care in Aboriginal communities [9][10][11][12]. Early diagnosis through effective clinical management is crucial in mitigating the risk of liver cancer and associated mortality in people living with CHB [13].…”
Section: Introductionmentioning
confidence: 99%